APPLICATION OF THE BUSINESS JUDGMENT RULE DOCTRINE RELATED TO LEGAL PROTECTION EFFORTS FOR BOARD OF DIRECTORS DUE TO THE EXISTENCE OF STATE FINANCIAL LOSSES IN THE MANAGEMENT OF REGIONAL OWNED ENTERPRISES - Nodi, Hamzar (Proceeding International Seminar of Islamic Studies, 2023)
The granting of authority to regional governments is also accompanied by the handover and transfer of financing. The most important source of financing is local revenue (PAD). PAD is regional income sourced from regional taxes, regional user fees, separated regional wealth management results, and other legitimate regional original income, which aims to provide flexibility to regions in exploring funding in the implementation of regional autonomy as an embodiment of the principle of centralization. . It cannot be denied that the continuity and success of a BUMD company will greatly depend on the quality of the Board of Directors in driving the wheels of the company. Directors are required to be able to advance the company so that it always grows and is able to compete with competitors, so that it can survive, excel and have quality. This goal can only be achieved if the Board of Directors is able to issue appropriate policies and dare to take business risks. In accordance with the idiom "high risk high return", high risk will bring high returns. For this reason, in order to encourage Directors to dare to take business risks for the benefit of the Company, legal umbrellas such as the business judgment rule doctrine have a very essential role.